(untitled) (Baltimore, 1999)
This purposes of the book are to provide an in-depth account of the evaluation, management and long term course of those common clinical problems that require either referral for speciallized care or hospitalization and for appreciating the expected course of those problems.
Keywords: Family medicine,Ambulatory medical care,Ambulatory Care,Y học gia đình,Chăm sóc ngoại trú